1997
DOI: 10.1007/s002030050465
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of the nv- gvpACNOFGH gene cluster involved in gas vesicle formation in Natronobacterium vacuolatum

Abstract: The haloalkaliphilic archaeon Natronobacterium vacuolatum forms cylinder-shaped gas vesicles throughout the growth cycle when grown in media containing 15-25% NaCl. Cells cultivated in media containing 13% NaCl are, however, gas-vesicle-free. The major gas vesicle structural protein, nv-GvpA, was detected by an antiserum raised against the gas vesicles of Haloferax mediterranei; the antiserum reacted with an 8.3-kDa protein in samples containing cell extracts or purified gas vesicles of N. vacuolatum. The gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This was further confirmed by the observation of laddering of GvpL protein on gels. These genetic and biochemical results are consistent with the findings of comparative genomic studies, which showed that the corresponding gvp genes are present in all gas vesicle containing organisms examined [71,74-77]. …”
Section: Experimental Studies Of Gene Systemssupporting
confidence: 90%
“…This was further confirmed by the observation of laddering of GvpL protein on gels. These genetic and biochemical results are consistent with the findings of comparative genomic studies, which showed that the corresponding gvp genes are present in all gas vesicle containing organisms examined [71,74-77]. …”
Section: Experimental Studies Of Gene Systemssupporting
confidence: 90%
“…Cylindrical gas vesicles are also found in Halorubrum (Natronobacterium) vacuolatum isolated from the Kenyan alkaline soda lake Magadi, but they are only produced in media containing more than 15% salt (Fig. 1B) (Mwatha and Grant 1993;Mayr and Pfeifer 1997). The most unusual haloarchaeon is the large and square, but extremely thin gas-vesiculate Haloquadratum walsbyi (Fig.…”
Section: Gas Vesicles Of Halophilic Archaeamentioning
confidence: 94%
“…Haloferax mediterranei harbors the related mc-vac region that leads to cylinder-shaped gas vesicles (Englert et al 1992a), whereas the Halorubrum vacuolatum cluster consists of the single nvgvpACNOFGHIJKLM transcription unit (Fig. 8;Mayr and Pfeifer 1997;Pfeifer 2004). The two regulator genes gvpDE have not been found so far.…”
Section: Gas Vesicle Gene Clusters and Minimal Vac Regionmentioning
confidence: 96%
See 1 more Smart Citation
“…Genes encoding proteins involved in gas vesicle formation have been identified in a few species of cyanobacteria (Anabaena flos-aquae, Calothrix strain PCC 7601) and in halophilic archaea (Halobacterium salinarum, Haloferax mediterranei, and the haloalkaliphilic archaeon Natronobacterium vacuolatum) (6,10,14,20,21,27), as well as in the soil bacterium Bacillus megaterium (26). In the case of halophilic archaea, 14 gvp genes cluster in an approximately 9-kb DNA region termed the vac region (10,11,19,20).…”
mentioning
confidence: 99%